Analysis the Reality of Jordanian Olympic Sports Federations - Ali Abudari; Ayed Zureigat; Bashar Abdul Jawad; Osama Abdul Fattah (My University, 2017)
This study aimed at analysis the reality of Jordanian Olympic sports federations for individual and collective games, The subjects used consisted of (12) president Jordanian Olympic sports federations for individual games, and (4) collective games, where it was chosen deliberate way. As well as the researchers used a closed questionnaire included (45) paragraph, and other included (29) open questionnaire. To deal with the study sample data researchers used frequencies, percentages. The study results showed the individual sports Olympic federations, has strengths, including: interest in both sexes and all the age groups when developing federation plan. as well as the participation of general authority and the Federation Council in the development of the management plan for Federation, and all national team coaches have international and Asian training certificates of the strengths for collective sports game federations. as well as the Jordanian Olympic sports federations for individual and collective games suffering from weaknesses including: the weakness of the marketing process, and not to provide a psychological specialist, and not to providing financial support for scientific research, and poor strategic planning. The researcher recommends the importance of increase effectiveness of controls by the IOC through the formation a technical and administrative committee to follow up the annual plan for the Strategic Plan, and the trend towards the privatization of sports facilities to increase financial support to sports federations.

هدفت هذه الدراسة للتعرف إلى واقع الاتحادات الرياضية الاولمبية الاردنية للألعاب الفردية والجماعية، ولتحقيق ذلك قام الباحثون باستخدام المنهج الوصفي باسلوبه المسحي على عينة من (12) رئيس اتحاد رياضي للألعاب الفردية و(4) رؤساء للألعاب الجماعية. حيث تم اختيارهم بطريقة عمدية. واستخدم الباحثون استبانة مغلقة اشتملت على (45) فقرة، وأخرى مفتوحة تكونت من (29) تساؤل. ولمعالجة بيانات الدراسة استخدم الباحثون التكرارات والنسب المئوية. وأظهرت نتائج الدراسة أن الاتحادات الرياضية الاولمبية للألعاب الفردية تمتلك نقاط قوة منها: الاهتمام بكلا الجنسين، وكافة الفئات العمرية عند وضع خطة الاتحاد. كذلك مشاركة الهيئة العامة ومجلس ادارة الاتحاد في وضع خطة الاتحاد، ومن نقاط قوة الاتحادات الرياضية الاولمبية للألعاب الجماعية أن كافة مدربي المنتخبات الوطنية يحملون شهادات تدريبية دولية واسيوية. كذلك تعاني الاتحادات الرياضية الاولمبية للألعاب الفردية والجماعية نقاط ضعف منها: ضعف عملية التسويق، وعدم توفر المختص النفسي، وعدم توفير الدعم المالي للبحث العلمي. وضعف التخطيط الاستراتيجي. ويوصي الباحثون بضرورة زيادة فعالية الرقابة من قبل اللجنة الاولمبية من خلال تشكيل لجنة فنية وادارية لمتابعة مدى ملائمة الخطط السنوية للخطة الاستراتيجية، والتوجه نحو خصخصة المنشآت الرياضية لزيادة الدعم المالي للاتحادات الرياضية.
تحليل واقع الاتحادات الرياضية الاولمبية الاردنية